PENDAMPINGAN BELAJAR SISWA SEKOLAH DASAR UNTUK MENINGKATKAN KEMAMPUAN CALISTUNG - Nyoman Ayu Putri Lestari (Jurnal Abdimas Ilmiah Citra Bakti, 2024)
This study focuses on the learning assistance at Rumah Baca Loloan aimed at improving the reading, writing, and arithmetic (calistung) skills of elementary school students. The background of this research is the concern over the low calistung abilities among elementary school students, which could potentially hinder their academic performance in the future. This assistance program is implemented in response to the urgent need to improve basic skills through a more personalized and supportive learning approach. The assistants, consisting of trained PGSD students, pay special attention to the students, ensuring they receive the necessary help to overcome learning difficulties. The results of the assistance show a significant improvement in the students' calistung abilities after participating in this program. Indicators of improvement include increased reading fluency and text comprehension, improved writing skills with correct spelling and sentence structure, as well as increased speed and accuracy in basic arithmetic. Additionally, there is an increase in students' motivation to learn and self-confidence. The significance of these findings is that learning assistance outside of formal school hours can play an important role in enhancing students' basic skills. Support from parents and the community also proves to be crucial in the success of this program. The importance of this service lies in the evidence that structured and sustained interventions can have a significant positive impact on students' academic development, highlighting the need to expand similar programs to reach more students in need.